Representation of Islamic Communication Ethics in Etnis Gayo Cultural Culture in Aceh Central District (Representasi Etika Komunikasi Islam dalam Budaya Tutur Etnis Gayo di Kabupaten Aceh Tengah) - nfn Marhamah (Jurnal Pekommas, 2018)
This study discusses the verbal symbols of Islamic communication ethics in Gayo ethnic speech in Central Aceh District. Speech in Gayo culture is a greeting or call between individuals, between groups or individuals with groups. In Gayo culture, it is unethical to call someone by name directly. Speech in Gayo culture is placed in the context of the kinship system and social structure. The method used in this research is qualitative research with ethnographic approach of communication. While the data collection techniques used are observation, documentation, as well as interviews with customary figures or cultural figures, community leaders or elders, and the community. Then the data were analyzed using semiotics analysis of Roland Barthes version. The results of this study indicate that the verbal symbols of Islamic communication ethics in Gayo ethnic speech in Central Aceh Regency seen in the use of speech used in everyday life is based on kinship system or kinship and position or function (said degree). The denotative meaning in this speech can be understood from the meaning described in Gayo. While the connotative meaning in this speech is understood based on Gayo cultural values. Understanding the connotative meaning of this speech become a reference in using speech in accordance with the context that gave rise to the myth in Gayo culture called kemali, jis, moth and sumang.Penelitian ini membahas mengenai simbol-simbol verbal etika komunikasi Islam dalam budaya tutur etnis Gayo di Kabupaten Aceh Tengah. Tutur dalam budaya Gayo merupakan kata sapaan atau panggilan antar individu, antar kelompok atau individu dengan kelompok. Dalam budaya Gayo, tidak etis memanggil seseorang dengan menyebut namanya langsung. Tutur dalam budaya Gayo ditempatkan pada konteks sistem kekerabatan dan struktur sosial. Metode yang digunakan dalam penelitian ini adalah peneltian kualitatif dengan pendekatan etnografi komunikasi. Sementara teknik pengumpulan data yang digunakan adalah pengamatan, dokumentasi, serta wawancara dengan tokoh adat atau tokoh budaya, tokoh masyarakat atau sesepuh , dan masyarakat. Kemudian data dianalisis dengan menggunakan analisis semiotika versi Roland Barthes. Hasil penelitian ini menunjukkan bahwa simbol-simbol verbal etika komunikasi Islam dalam budaya tutur etnis Gayo di Kabupaten Aceh Tengah terlihat pada pemakaian tutur yang digunakan dalam kehidupan sehari-hari didasarkan pada sistem kekerabatan atau kekeluargaan dan jabatan atau fungsi (tutur gelar). Makna denotatif dalam tutur ini dapat dipahami dari arti yang dijelaskan dalam bahasa Gayo. Sedangkan makna konotatif dalam tutur ini dipahami berdasarkan nilai-nilai budaya Gayo. Pemahaman makna konotatif dari tutur ini menjadi acuan dalam memakai tutur sesuai dengan konteksnya yang menunculkan mitos dalam budaya Gayo disebut dengan kemali, jis, jengat, dan sumang.